Religion, ethnicity, and the secular world - Montero,Paula (2014)
This paper explores the contrastive, or even contradictory, relations established between 'religions' and 'ethnicities' and what is by convention called the secular world in the conception of contemporary multicultural and post-secular democracies. When and why are 'religions' and 'ethnicities' perceived as a challenge to the political system? We draw on the literature that addresses the challenges posed by the growing presence of Muslim populations in Europe in order to analyze the confrontation in Brazil between Neo-Pentecostal and Afro-Brazilian groups. Our purpose is to understand why, differently from the European conflict, in which Muslim minorities are perceived as a simultaneously ethnic and religious challenge, conflict in Brazil occurs in a doubly inverted relation. Afro-Brazilian religions have built a positive relation to Brazilian nationality and have been acknowledged as religions by the State. In contrast, Neo-Pentecostal religions, although legally recognized, are weakly connected to Brazilian nationality.